Kemajemukan dan Toleransi Beragama Masyarakat Tuban: Analisis Struktural Fungsional Talcott Parsons - Emi Fahrudi (Islam & Contemporary Issues, 2026)
This study examines the diversity and religious tolerance of the Tuban community using a qualitative research approach. The study involved key informants consisting of religious leaders, community leaders, cultural practitioners, and local residents selected through purposive sampling based on their knowledge and active involvement in interreligious social life. Data were collected through in-depth interviews, participant observation, and document analysis, and were analyzed using the interactive model of Miles, Huberman, and Saldaña, which includes data condensation, data display, and conclusion drawing and verification. Tuban, as a historic coastal trading region, has long served as a meeting point for traders from Arabia, Persia, China, and Gujarat, creating a pluralistic social structure characterized by ethnic and religious diversity. Although the majority of the population is Muslim, the presence of Christian, Catholic, Buddhist, Hindu, and Confucian communities reflects the region's multicultural character. The findings indicate that religious tolerance has developed through a long historical process of cultural acculturation reinforced by local traditions, shared cultural values, and religious social institutions. Talcott Parsons' structural-functional theory explains this social stability through the functions of adaptation, goal attainment, integration, and latent pattern maintenance. The practice of tolerance is reflected in mutual respect for places of worship, community participation in cross-cultural activities, and harmonious interreligious interactions. The study concludes that religious diversity has become a valuable social asset that strengthens social cohesion and enables the Tuban community to maintain harmony despite the potential for social conflict